Partisipasi Masyarakat Desa Kutapohaci Dalam Pembangunan Desa - Lesmana, Mega Fitria; Priyanti, Evi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Infrastructure development is a physical development process as a manifestation of the ideals of the state to create a prosperous and prosperous society evenly distributed in the territory of Indonesia, however, the infrastructure development which is the basis for the realization of a prosperous and prosperous society has not been obtained by the community if the cause is still apathetic towards society. development. Community participation is a form of participation to support a program in various ways. Through a participatory approach, community participation is not only limited to physical participation, but community involvement in contributing ideas and solving problems. Based on Law Number 6 of 2014 Article 78 concerning villages, it is expressly stated that village development aims to improve the welfare of rural communities and the quality of human life as well as poverty alleviation through meeting basic needs, developing village infrastructure and facilities, developing local economic potential, and utilizing natural resources. natural resources and the environment in a sustainable manner. However, the reality is that rural infrastructure development is contrary to the objectives of the applied law. The quality of development services in facilities and infrastructure cannot be felt by the community as a whole.